Avaliação da degradação de hidrocarbonetos por bactérias provenientes de compostagem - Araujo e Oliveira, Aline Marcia Silva [UNIFESP] (2016)
Composting is an alternative to convert organic waste into fertilizer which occurs predominantly by the action of microorganisms. Thus, it is expected that microorganisms capable of degrading various compounds inhabit compost bins. The aim of this study was to isolate hydrocarbon-degrading bacteria from composting. Three samples originated from a compost bin in the Fundação Parque Zoológico de São Paulo were studied using selective cultivation methods with poor nutrients media containing n-hexadecane as sole carbon source. Forty-four microorganisms were isolated and identified by mass spectrometry (MALDI-TOF) or sequencing of a 16S rRNA gene fragment. The isolates were identified as belonging to from the genus Acinetobacter, Pseudomonas, Stenotrophomonas, Gordonia, Elizabethkingia, Pandorea, Aquamicrobium, Bacillus, Klebsiella and Chryseobacterium. Three isolated from the genus Gordonia were submitted to growth curves and 2,6-DCPIP assays with different hydrocarbons as sole carbon source, and demonstrated ability to assimilate aliphatic hydrocarbons, and one of the isolates stood out from the others due to the increased growth in the media. The genomes of these 3 isolates were sequenced and bioinformatics analysis revealed the presence of CYP153 system, one of the systems responsible for starting the hydrocarbon degradation. qPCR experiments were performed in Gordonia isolates of the same species and through them it was verified that two genes from this system (ferredoxin and CYP153) have increased expression in both isolates in the presence of n-hexadecane in and dodecane when compared to the expression in the presence of glucose. However, a distinct profile in the growth curve as well as in the qPCR among isolates of the same species can be verified. The CYP153 system of the two isolates were cloned and expressed in E.coli BL21(DE3). Enzimatic activity of this system in E.coli could not be confirmed. The results demonstrate that the studied compost bins harbor microorganisms capable of expressing proteins responsible for hydrocarbon degradation.